Vitamin D Deficiency in Pregnancy: A Systematic Review - Fannysha Arrahma; Iche Andriany Liberty (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Vitamin D deficiency (VDD) is a common problem in reproductive-aged women and has become a major public health problem worldwide. Adverse health outcomes such as preeclampsia, low birthweight, neonatal hypocalcemia, poor postnatal growth, bone fragility, and increased incidence of autoimmune diseases have been linked to low vitamin D levels during pregnancy and infancy. A systematic literature search was performed on September 6th – 21st, 2022 using respected database. The identified articles were screened using the chosen eligibility criteria. Literature selection was performed with rest time restriction from January 1, 2017, and September 22, 2022 and restricted to only published in English articles. Three papers were evaluated in full-text after duplicates were removed. Tammo et al, Mansur et al and Moralez et al were the three studies that remained following full-text screening utilizing eligibility criteria and quality assessment showing a significant proof regarding this review. Vitamin D deficiency had wide variety of effects in pregnancy as it may increased risk of multisystem disorders in pregnancy such as preeclampsia, low birth weight in neonates, insulin resistance, gestational diabetes mellitus (GDM), and a higher risk of primary cesarean delivery. Optimal level of 30 ng/mL or more before conception and throughout the entire pregnancy with different dosages available, avoiding levels below 20 ng/ml.